The Effects of Informal Care Provision on Mental Health Across European Countries - Nolan, Andreas (My University, 2023)
Given Europe’s rapid population aging, it is important to consider whether countries on the continent are equipped to provide social services to their older inhabitants. Often, care work for older individuals is provided informally (i.e. unpaid) by family members, rather than through government services. Though engaging in helping behaviors can sometimes lead to positive health benefits, previous research has identified a number of physical and mental health declines that informal caregivers experience while engaging in particularly intensive care work. With data from waves 6, 7, and 8 (spanning the years 2015 to 2020) of the Survey of Health, Ageing, and Retirement in Europe (SHARE), I used panel fixed-effects models to examine within-person variation in depression scores after a respondent starts providing daily or almost daily informal care. I focused specifically on differences between caregivers providing informal care inside their home versus those providing it outside their home. The final sample encompassed 18 countries and contained 23,488 respondents when observing informal care inside the home and 31,481 respondents when observing informal care outside the home. Overall, my results substantiate previous research that has found that the effect of informal caregiving on depressive symptoms is more pronounced for in-home versus out-of-home caregivers. However, my research strengthens this claim through a more precise comparison of these two informal caregiving contexts by isolating the specific type of care work provided and time commitment involved. In addition, my results show that belonging to a larger household minimizes the declines in mental health from providing personal care outside the home, and there is preliminary evidence to suggest that countries with greater government responsibility for long-term care dampen the depressive consequences of providing care inside the home. Further, countries with greater governmental responsibility for long-term care provision appear to be more successful at shrinking the pool of informal caregivers that provide particularly intensive forms of care. Together, these findings underscore that policy interventions designed to assist informal caregivers must take into consideration a wide constellation of potential caregiving relationships and place renewed attention towards out-of-home caregivers. Still, more comprehensive social support metrics are needed to understand how social support can buffer the emotional burden of caregiving work.
Keywords: Informal care, long-term care, mental health, caregivers, international comparison, longitudinal study, social support